‫اثر‬‫التمويل‬ ‫السندي‬ ‫على‬ ‫قيمة‬ ‫المؤسسة‬ ‫الإقتصادية‬ ‫دراسة ‬‫حالة‬ ‫مجمع‬ ‫سونلغاز‬ ‫(‬‫‪2011‬‬‫‪/‬‬‫‪2015‬‬‫)‬ - ‫وفاء ‫سلاطنية‬ ‬; ‬ ‫ايمان ‫بشيحي‬ (My University, 2017)
The economic institution has many sources of funding, which gives it the opportunity to diversify and choose. This is to find the optimal financing mix that balances the return and the risk. Most institutions resort to the financial market as an external source that provides them with two financing alternatives: property rights and debt. This is appropriate for the trade-off between these two alternatives. Both funding cost and the financial leverage are instrumental factors that make up the financial structure of the company, They are different from the loan capital option, for they enable more profitability thanks to their low and steady costs, on the other hand, financing through debt, is more costly and riskier, whereby, The company is required to reimburse the loan along with interests according to the schedule agreed upon, regardless of its solvency. It also has a direct impact on the value of the institution and its financial position, which has always been the focus of debate among economic thinkers on how the financing structure affects the value of the institution it is necessary to study and measure the impact of this source on the value of the institution by studying a set of ratios of the structure of financing and profitability, in addition to knowing the impact and degree of financial leverage and calculating the value of the institution by following one of the entrances. The study is being carried out at the SONALGEZ complex in Algeria.